A standing vehicle occupant is likely to sustain a more severe injury than one who has flexed knees in an under-vehicle explosion: A cadaveric study - Masouros,SD; Newell,N; Bonner,TJ; Ramasamy,A; Hill,AM; West,ATH; Clasper,JC; Bull,AMJ (2012 Ircobi Conference Proceedings International Research Council on the Biomechanics of Injury, 2012)
The lower limb of military vehicle occupants has been the most injured body part due to undervehicle explosions in recent conflicts. Understanding the injury mechanism and causality of injury severity could aid in developing better protection. Therefore, we tested 4 different occupant postures (seated, brace, standing, standing with knee locked in hyper-extension) in a simulated under-vehicle explosion (solid blast) using our traumatic injury simulator in the laboratory; we hypothesised that occupant posture would affect injury severity. No skeletal injury was observed in the specimens in seated and braced postures. Severe, impairing injuries were observed in the foot of standing and hyper-extended specimens. These results demonstrate that a vehicle occupant whose posture at the time of the attack incorporates knee flexion is more likely to be protected against severe skeletal injury to the lower leg.